Accuracy of visual inspection with acetic acid for cervical pathology screening in low cost setup - Sisodia, Aditya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Cancer cervix, a preventable disease continues to be a cause of great concern to women’s health, being associated with agonizing morbidity and high mortality. Approximately 493,100 new cases and more than 273,000 deaths occur each year, among women worldwide.IN India the screening is largely based on pap smear, which is cumbersome procedure due to transportation of samples and follow up of patients are not usually feasible. Visual inspection with Acetic acid (VIA) is simple and easy to teach procedure. Follow-up of patients usually doesn’t require. Methods: This study includes a total of 1000 patients who attended OPD of gynecology. Each patient is subjected to VIA examination. Biopsy is taken from women with abnormal findings on VIA. The objectives of this study were to evaluate the sensitivity and specificity and positive predictive value of inspection of cervix with acetic acid in precancerous lesions of cervix. Results: When biopsy is taken as reference standard, VIA has sensitivity of 97.7%, specificity of 76.6%, PPV of 62.9% and NPV of 98.5%. The accuracy rate for VIA is 84.8%. Conclusions: VIA is highly sensitive for diagnosis and treatment of cervical pathology at the same sitting. It can be done cost effectively in low resource set up.